2017
DOI: 10.1016/j.ypmed.2017.05.021
|View full text |Cite
|
Sign up to set email alerts
|

High-risk human papillomavirus detection in self-sampling compared to physician-taken smear in a responder population of the Dutch cervical screening: Results of the VERA study

Abstract: In 2017 the cervical cancer screening program in The Netherlands will be revised. Cervical smears will primarily be tested for the presence of high-risk human papillomavirus (hrHPV) instead of cytology, and vaginal self-sampling will be offered to non-responders. This includes a potential risk that part of the women who would otherwise opt for a cervical smear will wait for self-sampling. However, self-sampling for hrHPV in a responder population has never been studied yet. The aim of this study was to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 29 publications
8
71
3
2
Order By: Relevance
“…Yet, almost 10% reported uncertainty regarding sample collection and some stated the lack of a click when rotating the brush as their reason. Despite small numbers, this finding is higher than reported by Van Baars et al [10] (3.0%) and Ketelaars et al [9] (0.8%) who used the same device in a referral and screening population, respectively. This difference might be explained by the fact that the women in our study performed home-based self-sampling, whereas in the study by Van Baars et al [10] the women performed clinic-based self-sampling allowing them to ask questions and receive guidance.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Yet, almost 10% reported uncertainty regarding sample collection and some stated the lack of a click when rotating the brush as their reason. Despite small numbers, this finding is higher than reported by Van Baars et al [10] (3.0%) and Ketelaars et al [9] (0.8%) who used the same device in a referral and screening population, respectively. This difference might be explained by the fact that the women in our study performed home-based self-sampling, whereas in the study by Van Baars et al [10] the women performed clinic-based self-sampling allowing them to ask questions and receive guidance.…”
Section: Discussioncontrasting
confidence: 67%
“…Ketelaars et al [9] found no significant differences in HPV16/18 prevalence between samples, whereas the prevalence of HPV of other types was significantly higher in self-samples (8.0%) than in GP-collected samples (6.3%). We observed no significant differences in the HPV prevalence between samples, but the same trend was seen, especially for the prevalence of HPV of other types (21.1% versus 18.3%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-sampling can change this state of affairs by enabling screening programs to reach marginalized women and ultimately increase attendance. There is increasing evidence to that effect [11][12][13][14][15] . It stands to reason to assume that women who do not benefit from screening are also less likely to be reached by hpv vaccination programs 16 , which augments the disparity in health promotion that self-sampling can help reduce or eliminate.…”
Section: El Franco Mph Drph Frsc Fcahs Ocmentioning
confidence: 99%